2019
DOI: 10.1002/mame.201800755
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biocompatible and Antibacterial Collagen Hydrogels via Dialdehyde Polysaccharide Modification and Tetracycline Hydrochloride Loading

Abstract: Nowadays, collagen hydrogels with both good physicochemical and antibacterial properties for tissue engineering have drawn broad attention. Herein, a biocompatible and antibacterial collagen hydrogel is developed via alginate dialdehyde (ADA) modification and tetracycline hydrochloride (TC) loading based on Schiff's base formation. Fourier transform infrared spectroscopy and X‐ray diffraction spectra suggest the maintenance of collagen structure integrity after ADA modification. The modification significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…The chemical structure of the highly branched Alm in α- (1,4) bonds is linked to this antibacterial capacity; due to this, the lineal chains HEC and HPMC that do not present ramifications in their structures, they do not exhibit significantly antibacterial capacity. 39,40 Biomaterials in hydrogel state that have modulation in their degradation and mechanical properties, and that also exhibit antibacterial capacity, would show effective performance in biomedical applications such as wound healing dressings. This way the generation of bacterial infections would be controlled by avoiding the use of antibiotics or exogenous molecules that fulfill this function.…”
Section: Antibacterial Capacity Assessmentmentioning
confidence: 99%
“…The chemical structure of the highly branched Alm in α- (1,4) bonds is linked to this antibacterial capacity; due to this, the lineal chains HEC and HPMC that do not present ramifications in their structures, they do not exhibit significantly antibacterial capacity. 39,40 Biomaterials in hydrogel state that have modulation in their degradation and mechanical properties, and that also exhibit antibacterial capacity, would show effective performance in biomedical applications such as wound healing dressings. This way the generation of bacterial infections would be controlled by avoiding the use of antibiotics or exogenous molecules that fulfill this function.…”
Section: Antibacterial Capacity Assessmentmentioning
confidence: 99%
“…From Figure 5d, it can be found that the drug release time from the acid medium was 72 h, which was significantly longer compared to those of the previously reported PDA/CNF hydrogel (24 h) and CNF hydrogel (10 h). 13 In addition, the drug release time (72 h) of the MPDA@GO/CNF composite hydrogel was superior to other carriers such as collagen hydrogel (10 h) 53 and the ZIF-8@hyaluronic acid (HA) system (20 h), 54 which are listed in Table 1. As seen from Figure S9, the burst release amount (14%) during the first hour of TH release from the MPDA@GO/CNF composite hydrogel in PBS 7.4 solution was clearly lower than that of other carriers for the same drug (TH) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the release amount of CNF/CS beads (8:2) in the first 1 h of releasing under acid conditions (14.5%) was lower than other reported TH carriers, such as polydopamine/CNF hydrogel (20%) [ 6 ], collagen hydrogel (42%) [ 32 ], polycarboxybetaine hydrogel (35%) [ 33 ], and hyaluronic acid/alginate scaffolds (50%) [ 34 ]. Simultaneously, the total release amount of TH from CNF/CS beads (8:2) (88%) was higher than many reported TH carriers, such as polydopamine/CNF hydrogel (77%) [ 6 ], collagen hydrogel (50%) [ 32 ], and cellulose nanocrystal (82.2%) [ 35 ]. Additionally, the release amount in the first 1 h and the total release amount of TH were comparable with the specially designed mesoporous polydopamine/graphene oxide/CNF (MPDA/GO/CNF) hydrogel with an encapsulation structure (14% and 84.3%, respectively) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%